2015
DOI: 10.1001/jamapsychiatry.2015.0226
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Development of Brain Connectivity in Adolescents With Schizophrenia and Their Unaffected Siblings

Abstract: IMPORTANCE Abnormalities in structural brain connectivity have been observed in patients with schizophrenia. Mapping these abnormalities longitudinally and understanding their genetic risk via sibship studies will provide crucial insight into progressive developmental changes associated with schizophrenia.OBJECTIVES To identify corticocortical connections exhibiting an altered developmental trajectory in adolescents with childhood-onset schizophrenia (COS) and to determine whether similar alterations are found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 52 publications
5
39
0
Order By: Relevance
“…Converging evidence supports the notion that wiring disruptions of brain networks may partially underlie these abnormalities (5)(6)(7). Indeed, previous studies have found marked differences in the brain network architecture in schizophrenia (8,9) and delineated alterations in their structural development (10). More generally, human brain networks show a complex architecture favoring topologically advantageous properties while still being sparsely connected, in line with the proposal that the developmental architecture of the human brain connectome results from an economic trade-off between minimizing wiring costs and allowing adaptively valuable topological features (11).…”
Section: Introductionsupporting
confidence: 53%
“…Converging evidence supports the notion that wiring disruptions of brain networks may partially underlie these abnormalities (5)(6)(7). Indeed, previous studies have found marked differences in the brain network architecture in schizophrenia (8,9) and delineated alterations in their structural development (10). More generally, human brain networks show a complex architecture favoring topologically advantageous properties while still being sparsely connected, in line with the proposal that the developmental architecture of the human brain connectome results from an economic trade-off between minimizing wiring costs and allowing adaptively valuable topological features (11).…”
Section: Introductionsupporting
confidence: 53%
“…In humans, the differential variance contained within cortical morphology and structural network architecture could be investigated through further within-population comparisons of these measures, in (1) their ability to discriminate between case–control populations, (2) their association to behavioral and cognitive measures, and (3) their heritability. For example, patients with childhood-onset schizophrenia have shown differences in adolescent trajectories of both cortical thinning (Alexander-Bloch et al 2014) and structural correlation (Zalesky et al 2015) relative to healthy controls, but the measures have not been explicitly compared.…”
Section: Discussionmentioning
confidence: 99%
“…This derives from the notion that individuals at heightened risk for a schizophrenia-spectrum disorder (but who do not develop the illness) show a normalisation of abnormalities as they mature into adulthood. This is evidenced in studies examining trajectories of brain development in the unaffected siblings of childhood schizophrenia cases [60][61][62] (for discussion: 10,11,16]). Specifically, abnormalities found in childhood and early adolescence normalise during adolescence, including evidence of increased brain volumes and brain connectivity.…”
Section: Implications For Interventionmentioning
confidence: 99%